PENGGUNAAN MULTIMEDIA INTERAKTIF MODEL TUTORIAL UNTUK MENUMBUHKAN MINAT BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Arwinda, Putri; Prastowo, Andi; Noptario, Noptario (Jurnal Dedikasi Pendidikan, 2024)
This study aims to describe how the implementation of learning using interactive multimedia tutorial models to foster students' interest in learning. The research used in this study with a qualitative approach descriptive method. Data collection techniques in this study were carried out through observation and interviews. This research was conducted at State Elementary School 1 Maguwoharjo. The subjects in this study were two class teachers, class IV A teacher and class IV B teacher. Data analysis techniques in this study were carried out using thematic data analysis. The results of this study reveal the implementation of learning by using interactive multimedia tutorial models. In the implementation of tutorial-based learning, there are obstacles such as weak network access and frequent electrical power outages. However, these obstacles can be overcome by increasing the wifi speed and increasing the electric power. Based on the results of the interviews, it shows that the use of interactive multimedia tutorial models can have a positive impact on student interest in learning, which is characterized by active participation, improved academic grades, better attendance, and positive feedback from students, so that through this study, researchers can recommend the use of interactive multimedia tutorial models in other schools in an effort to foster student interest in learning